Debt Limits and the Structure of Public Debt - Pienkowski, Alex (IMF Working Papers; Working Paper ;, 2017)
This paper provides a tractable framework to assess how the structure of debt instruments-specifically by currency denomination and indexation to GDP-can raise the debt limit of a sovereign. By calibrating the model to different country fundamentals, it is clear that there is no one-size-fits-all approach to optimal instrument design. For instance, low income countries may find benefit in issuing local currency debt; while in advanced economies debt tolerance can be substantially enhanced through issuing GDP-linked bonds. By looking at the marginal impact of these instruments, the paper also provides insight into the optimal portfolio compostion.